1995
DOI: 10.1084/jem.182.6.1973
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-XL displays restricted distribution during T cell development and inhibits multiple forms of apoptosis but not clonal deletion in transgenic mice.

Abstract: The survival of T lymphocytes is tightly controlled during development. Here, we show that Bcl-xL, a protein homologue of Bcl-2, is highly regulated in the thymus in a pattern different than that of Bcl-2. The maximum expression was in CD4+CD8+ thymocytes, a developmental stage where Bcl-2 is downregulated. To assess the role of Bcl-xL in thymocyte apoptosis, we generated mice overexpressing an E mu-bcl-x transgene within the T cell compartment. Constitutive expression of Bcl-xL resulted in accumulation of thy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
137
0
1

Year Published

1998
1998
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(156 citation statements)
references
References 60 publications
18
137
0
1
Order By: Relevance
“…It has been reported that, in contrast to thymocytes and transformed T cells, normal mature T cells may be independent of Bcl-xL as a result of high Bcl-2 expression (Grillot et al, 1995). This was elegantly confirmed in a Bcl-xL conditional knockout mouse.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It has been reported that, in contrast to thymocytes and transformed T cells, normal mature T cells may be independent of Bcl-xL as a result of high Bcl-2 expression (Grillot et al, 1995). This was elegantly confirmed in a Bcl-xL conditional knockout mouse.…”
Section: Discussionmentioning
confidence: 80%
“…The knockout mouse model showed that, as with Bcl11b, deficiency of Bcl-xL led to massive apoptosis of hematopoietic cells, and impaired maturation and shortened lifespan of lymphocytes (Motoyama et al, 1995). In turn, overexpression of Bcl-xL within the Tcell lineage resulted in accumulation of thymocytes in lymphoid organs and increased resistance to apoptosis (Grillot et al, 1995). Moreover, overexpression of BclxL was detected in T-ALL and ATLL cell lines and samples, and its suppression by anti-sense approaches induced apoptosis and sensitized T-ALL cells to chemotherapeutic drugs (Mori et al, 2001;Broome et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are subtle differences between these 2 lines of Bcl-x L transgenic mice. First, the Bcl-x L transgene used in transplantation and EAE studies was under the control of the E promoter/ enhancer (12), while the Bcl-x L transgene used in this study was under the control of the lck promoter (10). However, since both transgenes are targeted to the T lineage, it seems unlikely that phenotypic differences in these 2 lines are due to differences in promoter/ enhancer elements.…”
Section: Discussionmentioning
confidence: 99%
“…During T lymphocyte development, the expression of Bcl-x L is tightly regulated [20,21]. Bcl-x L is not expressed at DN or SP stage.…”
Section: Anti-apoptotic Bh1-4 Subfamilymentioning
confidence: 99%